Bianchi Stress Questionnaire - Bianchi, Estela Regina Ferraz (Revista da Escola de Enfermagem da USP, 2009)
The Bianchi Stress Questionnaire was built and validated to assess the stress level of hospital nurses. The questionnaire is self-applicable, composed of 51 items, and divided into six subscales, each receiving a score that ranges from 1 to 7. Subscales are composed of activities that involve nursing care and management. The use of this questionnaire highlights the most stressing subscale for either groups of nurses or for each individual, and also assesses the most stressing activities in the researched institution. The questionnaire is a supportive instrument in the decision-making process towards the implementation of strategies to cope with the hospital nurse's stress.